Prime Minister's Decree No. 590 of the year 2020 Promulgating The Executive Regulations of the Law on the Public Places Issued by Law No. 154 of teh Year 2019 = قرار رئيس مجلس الوزراء رقم 590 لسنة 2020 بإصدار اللائحة التنفيذية لقانون المحال العامة الصادر بالقانون رقم 154 لسنة 2019 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic